2020
DOI: 10.1038/s42003-020-01305-5
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion ribonucleoprotein complex proteins are major humoral cancer antigens and targets in autoimmune diseases

Abstract: Despite the accumulating evidences of the significance of humoral cancer immunity, its molecular mechanisms have largely remained elusive. Here we show that B-cell repertoire sequencing of 102 clinical gastric cancers and molecular biological analyses unexpectedly reveal that the major humoral cancer antigens are not case-specific neo-antigens but are rather commonly identified as ribonucleoproteins (RNPs) in the focal adhesion complex. These common antigens are shared as autoantigens with multiple autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“… 17 To determine the precise chemical structures of the sulfated GAG Ags, we used a GAG library covering diverse sulfation patterns (Figure 1A,B ). We performed GAG ELISA using 30 tumor‐infiltrating dominant Ig clones identified from the repertoire sequencing of 102 gastric cancers 16 , 17 and additional 27 pancreatic cancers (Figure 1A ). Five high‐affinity and five low‐affinity anti‐sulfated GAG clones, including those previously reported, 17 were identified (Figure 1C ; Figure S1B,C ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 17 To determine the precise chemical structures of the sulfated GAG Ags, we used a GAG library covering diverse sulfation patterns (Figure 1A,B ). We performed GAG ELISA using 30 tumor‐infiltrating dominant Ig clones identified from the repertoire sequencing of 102 gastric cancers 16 , 17 and additional 27 pancreatic cancers (Figure 1A ). Five high‐affinity and five low‐affinity anti‐sulfated GAG clones, including those previously reported, 17 were identified (Figure 1C ; Figure S1B,C ).…”
Section: Resultsmentioning
confidence: 99%
“…We also searched for protein Ags for the 30 dominant Ig clones found in human gastric or pancreatic cancer environments, discovering 10 protein Ags, including those previously reported (Figure 2 ; Figure S1C ). 16 , 17 The remaining 10 clones were still orphan Igs due to possible difficulties in technical conditioning. Therefore, it was surprisingly shown that half (10/20) of the dominant clones with defined Ags, in human tumor environments, commonly recognized dsGAG.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations